Tensile fracture strength of boron/aluminum laminates with holes and slits - Potti P.K.G.; Rao B.N.; Srivastava V.K. (My University, 2025)
This paper improves the stress fracture criteria proposed by Whitney-Nuismer known as the point stress criterion (PSC) and the average stress criterion (ASC), to predict the strength of composite laminates containing holes and slits. A simple relation is used for the characteristic length to improve the accuracy while evaluating the notched strength of laminates. The applicability of the proposed approach is examined by considering the notched strength data on carbon/epoxy and boron/aluminum laminates. The analytical results obtained in the present study correlate well with the test results of different notched configurations. This study confirms that the present modification in the stress fracture criteria can be used for notched strength evaluation of composite laminates. © 2001 Elsevier Science B.V. All rights reserved.